Physiological aspects of marathon running - Sperlich, B. (Marathon running: Physiology, psychology, nutrition and training aspects, 2016)
Marathon running has evolved as one of the world`s popular running experiences. Independent of the runner`s performance level the marathon event represent a major challenge to the runner`s biology. Multiple integrated physiological processes operate to resist fatigue during marathon running. The physical preparation for a marathon involves a series of complex biological adaptations to counteract exercise induced fatigue. The following chapter aims at describing important physiological components that are proposed to constrain a champion`s physiological capacity for ultimate endurance performance. Further, potential limiting factors of the lungs, cardio-vascular system, blood oxygen carrying capacity, muscle properties and metabolism are explained in order to understand the underlying mechanisms for developing specific training methods and to estimate the race pace during marathon running. Other important biological aspects involved in marathon running such as nutrition, thermoregulation, biomechanics will be discusses in detail in the following chapters